2022
DOI: 10.3389/falgy.2022.981961
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric eosinophilic esophagitis outcomes vary with co-morbid eczema and pollen food syndrome

Abstract: BackgroundEosinophilic esophagitis (EoE) is a chronic immune-mediated inflammatory disease characterized by eosinophil inflammation of the esophagus. It has been described as a component of the Allergic March and is often seen with other atopic diseases. Some atopic diseases, including asthma, are known to be heterogenous with endotypes that guide treatment. Similarly, we propose that EoE is a heterogenous disease with varying phenotypes and endotypes that might impact response to therapy.MethodsA single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…4 In adult patients with EoE, another well-defined IgE mediated reaction triggered by food is PFAS however, data in children with EoE is limited. [10][11][12][13] PFAS was reported in two retrospective case series of pediatric EoE between 0% and 5.1%. 10,13 Although not the primary aim, we found that PFAS in children with EoE is more common (15.3%) than previously reported.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4 In adult patients with EoE, another well-defined IgE mediated reaction triggered by food is PFAS however, data in children with EoE is limited. [10][11][12][13] PFAS was reported in two retrospective case series of pediatric EoE between 0% and 5.1%. 10,13 Although not the primary aim, we found that PFAS in children with EoE is more common (15.3%) than previously reported.…”
Section: Discussionmentioning
confidence: 98%
“…[10][11][12][13] PFAS was reported in two retrospective case series of pediatric EoE between 0% and 5.1%. 10,13 Although not the primary aim, we found that PFAS in children with EoE is more common (15.3%) than previously reported. In addition, all PFAS and one FIRE cases had comorbid AR similar to adult case series with FIRE.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation